Perception of the role of culture in the development of small cities by local governments in the context of strategic documents – a case study of Poland - Środa-Murawska Stefania; Biegańska Jadwiga; Dąbrowski Leszek (Bulletin of Geography. Socio-Economic Series)
It is widely accepted that the cultural sector and the creative sector have an impact on the socio-economic revival of cities. They create urban images, form a specific creative milieu, generate new jobs, and organize urban space. The above-mentioned observations have been mainly referred to the largest cities. So far, small cities have not been the subject of similar considerations. As many studies have shown in recent years, the potential of culture for socio-economic development in small cities has been noticed more and more often. It refers mainly to countries in Western Europe or in North America where generally, in the 1980s, the cultural sector was perceived as a remedy for the problems of post-industrial cities. This paper discusses the role of culture in the development of small cities in Poland, i.e. in a country in which only after 1989 is it possible to consider local development managed by local communities. The paper aims at showing how local governments of small cities in Poland perceive the role of culture in their development. The study is based on the analysis of strategic documents dedicated to the development of individual cities. When analysed, strategic documents clearly indicate that local authorities in every city use and are planning to further use different types of cultural activities for the enhancement or development of selected elements included in the broadly-understood socio-economic development; however, only few small cities notice the wide array of opportunities for making the cultural sector a base for socio-economic development.